2011
DOI: 10.3989/gya.091810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a vegetable fat blend on the texture, microstructure and sensory properties of kashar cheese

Abstract: The possibility of using a commercial vegetable fat blend in Kashar cheese was investigated. Kashar cheeses were manufactured by replacing the milk fat (MF) with a vegetable fat (VF) blend. Kashar cheeses from whole milk were also manufactured to compare textural, microstructural, meltability, color and sensory characteristics during a ripening period of 90 days. The use of vegetable fat decreased the meltability, hardness, cohesiveness, gumminess and chewiness of the cheese; while increasing adhesiveness wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
7
29
0
Order By: Relevance
“…Tyr: Tyrosine, Phe: Phenylalanine, Trp: Tryptophan chewiness and gumminess at the 90 th day of ripening (p<0.05). Dinkci et al (2011) found that the use of vegetable fat caused a decrease of hardness, cohesiveness, gumminess, and chewiness in kashar cheese whilst adhesiveness and springiness values were not affected. In another study, the reduction of fat content of Hallomi cheese caused an increase of hardness and chewiness values (Lteif et al 2009).…”
Section: Textural Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Tyr: Tyrosine, Phe: Phenylalanine, Trp: Tryptophan chewiness and gumminess at the 90 th day of ripening (p<0.05). Dinkci et al (2011) found that the use of vegetable fat caused a decrease of hardness, cohesiveness, gumminess, and chewiness in kashar cheese whilst adhesiveness and springiness values were not affected. In another study, the reduction of fat content of Hallomi cheese caused an increase of hardness and chewiness values (Lteif et al 2009).…”
Section: Textural Propertiesmentioning
confidence: 92%
“…Moreover, in recent years, cheese products wherein the milk fat is replaced with vegetable oils have gained increased popularity (Lobato-Calleros et al 1997;Bachmann 2001;Karvonen et al 2002;Kesenkas et al 2009;Arslan et al 2010a;Dinkci et al 2011). The use of vegetable oils can give the cheese a consistency that makes it more suitable for certain applications (Bachmann 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cohesiveness is a measurement of the extent to which the cheese can be deformed before it ruptures (Dinkci et al, 2011). In sensory terms it is the degree to which a substance is compressed between the teeth before it breaks.…”
Section: Textural Profile Of Cheese Samplesmentioning
confidence: 99%
“…Fat reduction in fresh white cheese resulted in more complete protein zones comprising the protein structure, increasing the degree of protein molecules cross-linking in the three dimensional network, and increasing resistance to deformation (Lobato-Calleros et al, 2007). In same manner, cheese elaborated with milk fat was more cohesive than the vegetable fat blend cheese (Dinkçi et al, 2011), and cheese cohesiveness decreases with fat content (Gunasekaran and Ak, 2000). It has been reported that the addition of palm oil decreased cheese hardness, probably due to the presence of fatty acids with lower melting point (Cunha et al, 2010).…”
Section: Texture Profi Le Analysismentioning
confidence: 89%